2023
DOI: 10.1126/sciadv.add4623
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-guided lipid nanoparticles deliver mRNA to the neural retina of rodents and nonhuman primates

Abstract: Lipid nanoparticle (LNP)–based mRNA delivery holds promise for the treatment of inherited retinal degenerations. Currently, LNP-mediated mRNA delivery is restricted to the retinal pigment epithelium (RPE) and Müller glia. LNPs must overcome ocular barriers to transfect neuronal cells critical for visual phototransduction, the photoreceptors (PRs). We used a combinatorial M13 bacteriophage–based heptameric peptide phage display library for the mining of peptide ligands that target PRs. We identified the most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 37 publications
0
62
0
1
Order By: Relevance
“…Herrera-Barrera et al identified peptides, which target PRs by utilizing a combinatorial M13 bacteriophage-based heptameric peptide phage display library. 76 The peptide, they found, SPALHFL, showed immediate localization to the PRs. Therefore, they prepared RNA-LNPs conjugated with the peptide, which successfully could deliver mRNA into RPE, Mu ¨ller glia, and PRs in mice and nonhuman primate, where LNPs were consisted of DMG-PEG2000, DSPC, cholesterol, and DLin-MC3-DMA as well as DSPE-PEG2000-conjugated MH43 peptide (SPALHFL-GGGSC).…”
Section: Targeted Therapy Using Rna-lnpsmentioning
confidence: 95%
See 3 more Smart Citations
“…Herrera-Barrera et al identified peptides, which target PRs by utilizing a combinatorial M13 bacteriophage-based heptameric peptide phage display library. 76 The peptide, they found, SPALHFL, showed immediate localization to the PRs. Therefore, they prepared RNA-LNPs conjugated with the peptide, which successfully could deliver mRNA into RPE, Mu ¨ller glia, and PRs in mice and nonhuman primate, where LNPs were consisted of DMG-PEG2000, DSPC, cholesterol, and DLin-MC3-DMA as well as DSPE-PEG2000-conjugated MH43 peptide (SPALHFL-GGGSC).…”
Section: Targeted Therapy Using Rna-lnpsmentioning
confidence: 95%
“…RNA-LNPs and other drugs typically accumulate in liver cells upon intravenous administration. 66 Several LNPs have been developed for the delivery of LNPs into targeted tissues by different administration routes in vivo, 48,[67][68][69][70][71][72] by adapting the specific lipid composition, 73,74 and by the addition of specific peptides, 55,[74][75][76] aptamers, 77 and ligands (Fig. 4).…”
Section: Targeted Therapy Using Rna-lnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…While viral vectors are highly efficient, LNPs are a potential alternative that have lower immunogenicity 7 and are less limited by cargo size. 8,9 In addition, the activity of LNPs is more transient compared to viral vectors, [10][11][12][13] making them well-matched to treat the acute phase of TBI within days to weeks of the injury. [14][15][16] LNPs are currently the most clinically advanced non-viral gene delivery vehicle, and multiple formulations have been approved by the FDA.…”
Section: Introductionmentioning
confidence: 99%